Models for upper levels of a hierarchy - Liu, Qing (Henry Stewart Talks, 2010)
Hierarchical Bayes models, The level-effect problem, Contextual influence, Range-frequency theory, Combining with distance-density theory, Model formalization, Web-based surveys, In-sample fit model comparison, Future research